2021
DOI: 10.3126/ijasbt.v9i3.39069
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antioxidant Studies of Green Synthesized Silver Nanoparticles using Azadirachta indica (Neem) Leaf Extract

Abstract: Silver nanoparticles (AgNPs) have been synthesized by green synthesis using Azadirachta indica leaf extract as both reducing and stabilizing agent. Synthesis of colloidal AgNPs was monitored by UV- visible spectroscopy. The UV- visible spectrum showed a peak at 455 nm corresponding to the plasmon absorbance of the silver nanoparticles. Crystallite structure of silver nanoparticles was studied using X-ray diffraction (XRD) analysis which revealed the face-centered cubic structure (FCC) with average particle siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…In the present study, the calculated crystallite size was found to be 9.6 nm was calculated by using the above equation, as shown in Table 3. The calculated crystallite value of thus obtained differed from the studies conducted previously 34,35 .…”
Section: Table 2: Antibiotic Sensitivity Test Of Microbes Isolated Fr...contrasting
confidence: 76%
“…In the present study, the calculated crystallite size was found to be 9.6 nm was calculated by using the above equation, as shown in Table 3. The calculated crystallite value of thus obtained differed from the studies conducted previously 34,35 .…”
Section: Table 2: Antibiotic Sensitivity Test Of Microbes Isolated Fr...contrasting
confidence: 76%